P1640COLONIZATION AND INFECTION WITH ESBL-PRODUCING AND CARBAPENEM-RESISTANT ENTEROBACTERIACIEAE IN KIDNEY TRANSPLANT RECIPIENTS: RISK FACTORS, IMPACT OF RENAL GRAFT FUNCTION AND USE OF HOSPITAL RESOURCES. (6th June 2020) - Palmisano, Alessandra; Salsi, Eleonora; Fenaroli, Paride; Degli Antoni, Anna Maria; Gandolfini, Ilaria; Ferrari, Carlo; Fiaccadori, Enrico; Maggiore, Umberto
Abstract: Background and Aims: ESBL-producing and carbapenem resistant (CR) Enterobacteriaceae are a common cause of severe infection, morbidity and mortality in kidney transplant recipients (KTR). Few studies have investigated the risk factors for ESBL-producing/CR Enterobacteriaceae colonization and infection in this group of patients, the effect of colonization and infection on KTR's renal graft function, and the use of hospital resources. Method: Retrospective follow-up study on a consecutive series of patients undergoing kidney transplantation at Parma University Hospital (Italy) between January-2016 and December-2018. We performed a multivariable-adjusted analysis of the predictive factor associated with MDR infection/colonization via general linear models for prevalence- and risk- ratio. Renal function (eGFR) decline was compared by mixed-effects random-coefficients models, hospital resources by negative binomial regression. Results: We enrolled 180 KTR (mean recipient's age: 52.4 [SD 12.4]; males 65%; mean donor's age: 54.6 [SD 15.6]) and followed them up for 2-years post transplantation. Cumulative prevalence of colonization 3-months post-transplantation and cumulative incidence of infection were 26.1% and 9.4% for ESBL, and 4.4% and 1.6% for CR. ESBL colonization was associated with hemodialysis vs peritoneal dialysis (93% vs 70% non-colonized; adjusted RR 0.21 [95% CI: 0.06 to 0.98]), dialysis vintage (mean months: 65 vs 42; adjusted associated with being above the median, RR 2.17 [95% CI: 1.32 to 3.55]) and retention of ureteral stent for more than one month after transplant (28% vs 12%; adjusted RR 2.09 [95% CI: 1.27 to 3.44]) ; ESBL infection was associated with retention of ureteral stent (47% vs 13%; adjusted RR 4.89 [95% CI 2.11 to 11.35]) whereas CR colonization was associated with surgical complication during transplant admission (50% vs 15%; adjusted RR 4.61 [95% CI 1.28 to 16.66]). Two patients (both with CR) died over the study follow-up, whereas none of the patients lost the graft. CR infection was associated lower baseline (3-months post-transplantation) eGFR compared to the other groups (-28.4mL/min/1.73m2 [95% CI: -50.5 to -6.3]); a numerically more rapid decline (up to - 5mL/min/year) of eGFR, albeit not statistically significant, was observed in patients with CR colonization compared to non-colonized at 2 years of follow-up. In comparison with non-colonized patients, adjusted mean days of carbapenem treatment in ESBL/CR colonized/infected was 5.7 vs 0.7 (P=0.003); length-of-hospital stay 5.8 vs 1.0 (P=0.055); days on drug-resistant-infection intravenous-outpatient-therapy 20.7 vs 0.1 (P= 0.008). Conclusions: The study shows that ESBL and CR colonization and infection in KTR are statistically associated with longer hemodialysis vintage, urological procedures, and surgical complications. They cause an increase in the hospital resources use and may jeopardize transplant outcomes.